Boom and Bust Patterns in the Adoption of Financial Innovations - Persons, John C.; Warther, Vincent A. (Review of Financial Studies, 1997)
We develop a dynamic model of the adoption of financial innovations. Each period, firms decide whether or not to adopt an innovation of uncertain value, and the profitability of each period’s adoptions reveals information about the innovation’s value. We show that characteristics of financial innovation waves cited by critics as evidence of irrational excess are, in fact, consistent with fully rational behavior. We also show that social welfare is enhanced when more firms adopt innovations of questionable value and that financial intermediaries have an incentive to encourage such adoption.